MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN BAGI ANAK AUTIS MELALUI MEDIA GAMBAR - Rido - Guspinal (Jurnal Penelitian Pendidikan Khusus, 2014)
This research is in the background by the background issues that appear in the field, the third class X autistic children in special schools sparkle Tarusan who have difficulty in understanding the content of reading simple sentences. This is evident from the beginning of the child's ability to understand the content of reading simple sentences children have difficulty on tests that researchers provide. children may not be able to answer all the tests with benar.Penelitian aims to improve the ability of autistic children to understand the content of reading simple sentences through media images. Image Media is a visual medium that can be used with ease in learning activities. Research methodology that researchers use a single subject research studies using AB designs. That is the design of a study comparing the ability to understand the content of a simple sentence reading in children with autism X between the baseline condition and the intervention condition.